Autoimmune thyroiditis: clinical presentation in a Nepalese population - Paudel, K; Paudel, B (Nepal Journal of Medical Sciences, 2014)
Background: Hypothyroidism has a wide range of clinical presentations. This study was conducted to describe the clinical manifestations of chronic Hashimoto`s thyroiditis (HT) in a Nepalese population. We also tried to identify symptoms or signs characteristic for HT. Methods: During the study period, all newly diagnosed patients with hypothyroidism were interviewed about symptoms, and clinical signs were assessed. The data of hypothyroid patients were divided in two groups: TPO antibody positive and TPO antibody negative. The symptoms and signs of the two groups were analyzed and compared. Results: Among the 88 hypothyroid patients, 33 (37.5%) had positive TPO antibody levels. Female patients were more likely to be TPO antibody positive (41.3% among female and 15.4% among male). The most frequent symptoms were lethargy, cold intolerance, constipation, tingling sensation and weight gain, and the most frequent signs were facial puffiness and non-pitting pedal edema, in both groups. Statistical analysis revealed, that cold intolerance, decreased appetite and insomnia were significantly more prevalent symptoms in the TPO antibody positive group (p<0.05). Conclusion: Hashimoto`s thyroiditis is a common cause of primary hypothyroidism. It is not possible to differentiate it from the clinical presentation. Nepal Journal of Medical Sciences | Volume 03 | Number 01 | January-June 2014 | Page 68-71 DOI: http://dx.doi.org/10.3126/njms.v3i1.10362